Efficacy of neuromuscular electro stimulation on muscle strength in elderly patients with diabetes mellitus underwent cardiovascular surgery – a multicenter randomized controlled trial. (25th November 2020) - Takino, K; Kameshima, M; Asai, C; Kawamura, I; Tomita, S; Hirakawa, A; Yamada, S
Abstract: Introduction: Cardiovascular surgery causes muscle weakness probably due to a postoperative increase in inflammatory cytokine production, and diabetes mellitus (DM) may promote the postoperative muscle weakness because of increased insulin resistance. Purpose: A multicenter randomized controlled trial was conducted to examine the effects of postoperative neuromuscular electrical stimulation (NMES) on muscle strength for elderly patients with DM after cardiovascular surgery (UMIN000029940). Methods: Patients underwent cardiovascular surgery were consecutive screened for eligibility (With DM and age ≥65 years) as study subjects. If eligible, patients were randomly assigned either to the NMES or the sham group. Both of group underwent NMES or sham stimulation (60 minutes / 5 times) and usual postoperative early mobilization program until postoperative day (POD) 7. The primary outcome was the percent change in knee extensor isometric muscle strength (%ΔKEIS) between preoperative to POD 7. Secondary outcomes were the percent change in usual (%ΔUsual walking speed) and maximum walking speed (%ΔMaximum walking speed) and grip strength (%ΔGS). Assessors for physical function were blinded to the outcomes. The statistician who was blinded to the allocation analyzed the data using preoperative value adjusted ANCOVA. Results: Of 1151 consecutive patients screened for eligibility from February 2018 to January 2020, 158 participants (NMES group, n=79; sham group, n=79) were enrolled. NMES group demonstrated significantly lower %ΔKEIS compared with those in the sham group (Table). Among secondary outcomes, NMES group showed significantly lower %ΔMaximum walking speed and tendency of lower %ΔUsual walking speed and %ΔGS (Table). Conclusion: NMES prevented postoperative muscle weakness in the elderly patients with DM, indicating that NMES along with early mobilization could be implicated as specific intervention to those populations. Funding Acknowledgement: Type of funding source: None